Moulding the story of Chaos : interpretation, perspectivity, and materiality - Quek, Yu Qing (Nanyang Technological University, 2021)
The parable of Chaos by Chinese philosopher Zhuangzi entreats its readers to refrain from imposing their will on nature— Chaos, or the primitive oneness of nature, slips from our grasp the more we attempt to improve or master it. In this spirit, however, any adaptation of Zhuangzi’s stories suffers from a performative contradiction: an adaptation dictates a commitment to a single interpretation of the parable over the universe of interpretive possibilities. This paper details my struggles and modest triumphs in adapting the parable of Chaos to a stop-motion film. I trace the development of my story and discuss the significance of including an unreliable student narrator, an educational context, a distinctive segment of Chaos’ reception, and the use of humour. Next, I examine how the medium of stop-motion and its materiality allow me to visually represent the parable in line with its guiding philosophy. In the last section, I reflect upon my project in its entirety. I elaborate on my newfound appreciation for interpretive biases and my realisation that my process of filmmaking can benefit from a Taoist reformation (that is, to direct and animate in a more spontaneous and effortless manner).